A Dark-Matter Search Using the Final CDMS II Dataset and a Novel Detector of Surface Radiocontamination - Ahmed, Zeeshan (California Institute of Technology, 2012)
Substantial evidence from galaxies, galaxy clusters, and cosmological scales suggests that ~85% of the matter of our universe is invisible. The missing matter, or "dark matter" is likely composed of non-relativistic, non-baryonic particles, which have very rare interactions with baryonic matter and with one another. Among dark matter candidates, Weakly Interacting Massive Particles (WIMPs) are particularly well motivated. In the early universe, thermally produced particles with weak-scale mass and interactions would `freeze out’ at the correct density to be dark matter today. Extensions to the Standard Model of particle physics, such as Supersymmetry, which solve gauge hierarchy and coupling unification problems, naturally provide such particles.

Interactions of WIMPs with baryons are expected to be rare, but might be detectable in low-noise detectors. The Cryogenic Dark Matter Search (CDMS) experiment uses ionization- and phonon- sensitive germanium particle detectors to search for such interactions. CDMS detectors are operated at the Soudan Underground Laboratory in Minnesota, within a shielded environment to lower cosmogenic and radioactive background. The combination of phonon and ionization signatures from the detectors provides excellent residual-background rejection.

This dissertation presents improved techniques for phonon calibration of CDMS II detectors and the analysis of the final CDMS II dataset with 612 kg-days of exposure. We set a limit of 3.8x10^(-44) cm^2 on WIMP-nucleon spin-independent scattering cross section for a WIMP mass of 70 GeV/c^2. At the time this analysis was published, these data presented the most stringent limits on WIMP scattering for WIMP masses over 42 GeV/c^2, ruling out previously unexplored parameter space.

Next-generation rare-event searches such as SuperCDMS, COUPP, and CLEAN will be limited in sensitivity, unless they achieve stringent control of the surface radioactive contamination on their detectors. Low-penetrating radiation, such as alpha and beta particles, will mimic signal in these experiments. This dissertation also presents the design and prototyping of a novel detector for surface radiocontaminants, called the BetaCage --- a neon-gas time projection chamber built from radiopure materials and operated underground with shielding similar to CDMS II. The BetaCage will enable beta screening of materials at world-best sensitivity of 10^(-5)/cm^2/keV/day, providing a valuable tool to the physics community.
Keywords: Dark Matter; Physics; WIMPs; CDMS; Cryogenic Dark Matter Search; Low-temperature detectors; Weakly Interacting Massive Particles